2018
DOI: 10.1111/ced.13368
|View full text |Cite
|
Sign up to set email alerts
|

Overweight and obesity may play a role in the pathogenesis of chronic spontaneous urticaria

Abstract: Our results suggest that CSU, especially if of long duration, may be associated with overweight and obesity, while increased body mass can result in later onset of urticaria symptoms. Further analyses to confirm the presented results and possible association between obesity and CSU occurrence are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
16
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 23 publications
3
16
2
1
Order By: Relevance
“…a BMI over 30 kg m −2 and the aggravation of CSU lesions after initiation of OMZ. The link between obesity and CSU has already been suggested in two previous studies 3,4 . The proportion of patients who were obese was significantly higher in the nonresponder group.…”
Section: Patients Characteristics Total Responders Nonresponders P‐vasupporting
confidence: 54%
“…a BMI over 30 kg m −2 and the aggravation of CSU lesions after initiation of OMZ. The link between obesity and CSU has already been suggested in two previous studies 3,4 . The proportion of patients who were obese was significantly higher in the nonresponder group.…”
Section: Patients Characteristics Total Responders Nonresponders P‐vasupporting
confidence: 54%
“…Our study also revealed that the incidence of ur caria was more among the pa ents who were overweight or obese which is also in accordance with other several studies 6,19 previously. This may be due to the fact that there are several evidences that prove obesity has been associated 20 with chronic low grade inflamma on and due to this obese person has decreased immune tolerance to an gens hence increasing the chances of allergies and other immune diseases due to the shi of balance towards T helper 2 21profile.…”
Section: Resultssupporting
confidence: 93%
“…Several risk factors such as the presence of autoantibodies, age older than 45 years, and vitamin D deficiency have been reported to be associated with longer duration of CSU [4][5][6][7] . A study of 85 CSU patients in Poland revealed that higher BMI values had a trend towards longer disease duration 8 .…”
mentioning
confidence: 99%
“…Zbiciak-Nylec et al 8 firstly reported that higher BMI values had a trend towards longer disease duration. In this study, we further revealed that higher WC rather than higher BMI is more related with the longer disease duration of CSU, although both WC and BMI can affect the disease duration.…”
mentioning
confidence: 99%